An Investigation of Church Based Peace Building Models in Selected Churches in Kericho County (British Journal of Multidisciplinary and Advanced Studies, 2022)
Peacebuilding with all members of the community in view of stemming potential and existing tension has become a necessity. In majority of politically and ethnically instigated violence, such as in the Kenyan post-election violence of 2008 and 2017, the Church was a major player in peace building processes as well as in the reconciliation process. This paper endeavoured to explore the available peace building models adopted by the Church in Kenya since 2008. To attain the mentioned objectives, the study engaged the Fowler theory of faith development. This was a qualitative research that applied the use of interviews and Focus Group discussions in the collection of primary data while secondary data used in this research was acquired through the review of documents and other relevant literature in public libraries and Church archives. Purposive sampling techniques were used to identify respondents, and the data analysed using context analysis. The study established Peace building models used by the Church were Mounting of Humanitarian Response Model and Policy advocacy which were done through Dialogue, Seminars, Evangelism, Sports and cultural events. These approaches to some extent helped to mitigate tension and violence in the region. Youth mentorship programs by the Church contributed to instilling the values of unity, honesty, peaceful co-existence as well as self-reliance among youth in the region and the society at large. The study recommends that religious organizations such as the National Council of Churches in Kenya (NCCK) and leaders should pursue peace building by ensuring that justice to all is achieved through methods that have respect for the people and also allow for the restoration of relations that foster and seek to correct injustices in regard to the fundamental values of human rights. The Kenyan Church should join many other faith-based peace advocates who endeavour to put into practise the principles of their belief in a manner that enables the building of local, regional, nationwide, as well as global machineries favourable for peace.